Familial Hemophagocytic Lymphohistiocytosis (FHL), Report of two Unique Cases - Mishra, Shubhankar; Agarwalla, Sunil Kumar; Behura, Sushree Smita; Pattnaik, Gouranga Charan (Journal of Nepal Paediatric Society, 2016)
Familial hemophagocytic lymphohistiocytosis (FHLH) is a rare genetic disorder associated with early onset in life with overwhelming activation of T lymphocytes and macrophages invariably leading to death. We present two cases of FHLH admitted to our hospital at different points of time. First child presented with multiple episodes of GTCS and high grade fever. There was a history of sibling death before. He was having hepatosplenomegaly with leucopenia, hyper-triglyceridemia, hyper-ferritinemia and bone marrow revealed abundant hemophagocytes in smear. Second case was a 6 month male with complaint of (Generalised Tonic Clonic Seizure (GTCS) with past history of repeated attacks of acute Respiratory Infection and neuroinfection. Previous sibling died in similar presentation. He was having hepatosplenomegaly, leucopenia, hyper triglyceridemia, hyper ferritinemia with abundant hemophagocytes in bone marrow smear. Both the cases were diagnosed as FHLH and treated according to protocol. Nepal Paediatr Soc 2015;35(3):283-286